Climate change, or climate shocks: What really triggers civil conflicts? - Sherin Khalifa; Svetlana Petri; Christian H. C. A. Henning (Kiel University, Department of Agricultural Economics, Chair of Agricultural Policy, 2020)
This paper provides an analysis of the impact of extraordinary climate shocks on the incidence of civil conflict using cross-country panel data from Africa and the Middle East (1981 to 2015). We find that: (i) The estimated impact of climate shocks (mainly temperature effect) on economic growth rate and domestic food production ranges from 3 to 5% compared to the estimated impact of temperature growth 47%. (ii) We identified a direct impact of climate shocks on the incidence of civil conflict, where this impact is similar in magnitude to the negative impact of rainfall growth on conflict (3-4%). (iii) We confirmed the negative link between conflict and both economic indicators, conflict begets next conflict, the positive impact of good governance and polity IV estimates, and the freshwater availability on reducing the risk of conflict. Concluding that the main effect of climate comes from the temperature growth effects and it is not extreme shocks that drive economic declines, which indicates that the climate rather operates in a non-linear process.
urn:nbn:de:gbv:8:3-2021-00234-5
Keywords: 330; Climate shocks; civil conflict; economic development